Singapore Airlines and flight SQ006 : managing an airline crisis - Henderson, Joan C. (2013)
Flight SQ006, operated by Singapore Airlines, crashed on 31 October 2000. The accident was the first with fatalities in the 28–year history of the airline, although all the passengers on board a plane of its wholly owned subsidiary (SilkAir) had died in a crash three years earlier. More accustomed to favourable reports associated with its successes, the airline now had to confront the challenges of managing a fatal accident and subsequent adverse publicity, which proved potentially damaging to its image and reputation. After dealing with the immediate consequences of the crash in the period up until 6 November, when final casualties were confirmed, there was an opportunity for the company in general, and the Public Affairs Department in particular, to pause and review the situation. Period covered 2000 – 2002